2022
DOI: 10.1007/s11886-022-01730-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Damage in COVID-19: What We Know Two Years Later

Abstract: Purpose of the Review The Coronavirus disease 2019 (COVID-19) pandemic has profoundly influenced cardiological clinical and basic research in the past two years. In the present review, we summarize the current knowledge on myocardial involvement in COVID-19, providing an overview on the incidence, the pathogenetic mechanisms, and the clinical implications of cardiac injury in this setting. Recent Findings The possibility of heart involvement in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…108 While early hypotheses invoked myocarditis, defined by the presence of inflammatory infiltrate along with nonischemic myocyte necrosis, as the cause of this acute heart failure-the true incidence of COVID-19 myocarditis remains uncertain and debated, but lower than initially reported. 23,63,65,68,[109][110][111][112] A large recent review of postmortem histopathologic data showed a high prevalence of myocardial necrosis and edema without myocarditis, owing to a lack of inflammatory infiltrate. 113 However, another up to date systematic review does show the presence of myocarditis, albeit infrequently, in available reported cases.…”
Section: Heart Failure and Myocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…108 While early hypotheses invoked myocarditis, defined by the presence of inflammatory infiltrate along with nonischemic myocyte necrosis, as the cause of this acute heart failure-the true incidence of COVID-19 myocarditis remains uncertain and debated, but lower than initially reported. 23,63,65,68,[109][110][111][112] A large recent review of postmortem histopathologic data showed a high prevalence of myocardial necrosis and edema without myocarditis, owing to a lack of inflammatory infiltrate. 113 However, another up to date systematic review does show the presence of myocarditis, albeit infrequently, in available reported cases.…”
Section: Heart Failure and Myocarditismentioning
confidence: 99%
“…41,[48][49][50][51][52][53][54][55][56][57] During the interval of 3 years, extensive work has aimed to understand the pathophysiologic basis for this injury, and to extrapolate how injury at the level of the viral particle and endothelial cell or cardiac myocyte begets injury at the level of the cardiovascular organ system as a whole, with particular attention paid to venous and arterial thrombosis, arrhythmias, acute coronary syndromes, myocarditis, and systolic dysfunction. 24,25,50,[58][59][60][61][62][63][64][65][66][67][68]…”
Section: Coronaviruses and The Cardiovascular System-overviewmentioning
confidence: 99%
“…Some of the most important questions concern the origins and causes leading to the severe form of COVID-19 or even death [6,7]. One of the most important pathological aspects of COVID-19 disease is its impact on the cardiovascular system, more specifically cardiovascular disease (CVD) [8][9][10][11]. The link between COVID-19 and CVD has been demonstrated and confirmed in numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 has been reported to produce multisystem ailments during the acute as well as post‐acute “long COVID” states (Cenko et al., 2021 ; Desai et al., 2022 ; Soriano et al., 2022 ). Cardiovascular consequences of COVID‐19 are attributed to a plethora of pathophysiological derangements including myocardial injury, myocarditis, endothelial dysfunction, vascular inflammation, oxidative stress, and a prothrombotic state (Behrooz et al., 2022 ; Nuzzi et al., 2022 ; Six et al., 2022 ). The largest cohort‐based study published to date on post‐acute cardiovascular outcomes in COVID‐19 survivors reports a substantial risk and 12‐month burden of incident cardiovascular diseases spanning ischemic, nonischemic heart diseases, and dysrhythmias emphasizing the need to integrate cardiovascular health monitoring into the care pathways of COVID‐19 survivors (Xie et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%